Semiotic Analysis Of The Index In Revealing RomanticismOn Poetry By Joko Pinurbo - Padli Alfareza; Samsiarni Samsiarni; Emil Septia (PT. Anagata Sembagi Education, 2024)
This research aims to examine the concept of romanticism as understood by Russell Noyes in the poetry of Joko Pinurbo, utilizing Charles Sanders Peirce's semiotic theory with a focus on the index as a key object. The study is conducted using a qualitative descriptive method, analyzing ten data points extracted from five of Joko Pinurbo's poems: